2022
DOI: 10.3390/cells11101605
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Long-Term Exercise and High-Fat Diet on Age-Related Telomere Shortening in Rats

Abstract: (1) Obesity and exercise are believed to modify age-related telomere shortening by regulating telomerase and shelterins. Existing studies are inconsistent and limited to peripheral blood mononuclear cells (PBMCs) and selected solid tissues. (2) Female Sprague Dawley (SD) rats received either standard diet (ND) or high-fat diet (HFD). For 10 months, half of the animals from both diet groups performed 30 min running at 30 cm/s on five consecutive days followed by two days of rest (exeND, exeHFD). The remaining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Although there was no change in capillary density, the number of small arteries increased in response to exercise suggesting improved myocardial vascularization (Figure 6C). This concept is substantiated by an increase in RTL, Terf-1, and Terf-2 expression in the aortic tissue of exercising animals (56). While moderate exercise has only mild cardiac effects, intensive exercise seems to induce cardiac hypertrophy, fibrosis, apoptosis, and inflammation in SD rats (57).…”
Section: Discussionmentioning
confidence: 95%
“…Although there was no change in capillary density, the number of small arteries increased in response to exercise suggesting improved myocardial vascularization (Figure 6C). This concept is substantiated by an increase in RTL, Terf-1, and Terf-2 expression in the aortic tissue of exercising animals (56). While moderate exercise has only mild cardiac effects, intensive exercise seems to induce cardiac hypertrophy, fibrosis, apoptosis, and inflammation in SD rats (57).…”
Section: Discussionmentioning
confidence: 95%
“…Both exercise and diet, but not their combination, had a significant impact on the body weight (Table S1). A thorough characterization of the animals, including food consumption, organ weight, lipid metabolism, and oxidative stress, has been published previously [42,43].…”
Section: Characterization Of Animalsmentioning
confidence: 99%
“…In animal studies, recent research on telomerase-deficient mice revealed that groups fed with a long-term n-3 PUFA-enriched diet (between 10–24 months) showed lower telomere attrition compared to the control group [40,41 ▪ ]. However, a study conducted on female Sprague Dawley rats showed no modification in telomere length or telomerase reverse transcriptase (TERT) expression in several tissues upon following a HFD rich in saturated fats [42]. Overall, while saturated fats intake seem to have deleterious effects on telomere length, n-3 PUFA consumption has been associated with reduce telomere attrition in both human and animal studies.…”
Section: Link Between Dietary Fat Telomere Length and Cognitive Functionmentioning
confidence: 99%